Thinking about What People Think about Nuclear Weapons. (1st January 2023) - Pelopidas, Benoît; Egeland, Kjølv
Abstract: What do people really think about nuclear weapons? Responding to Dill, Sagan, and Valentino's "Kettles of Hawks" in Security Studies 31, we examine the inconsistency between different surveys of public attitudes toward nuclear weapons use. We maintain that different survey techniques tap into disparate layers of opinion—each of which is "real" in their own way and of analytical value depending on the research question being asked. We conclude by reflecting on scholarly responsibility and the dilemmas associated with researching and communicating about potentially sensitive knowledge.